The Impact of Population Increase in the Educational Services Sector (Analytical Study in Lattakia) - Mohamed, Osama; Beshmane, shakib; Saeda, Ammar (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Teaching is a fundamental building block in development; it is a basic pillar for all prosperity plans and sustainable development in addition to the essential tasks related to social and cultural aspects. The relationship between education and people is mutual in that they affect and get affected by each other. The more education spreads, the better the lifestyles become. However, when populations raise dramatically, the educational system gets affected both qualitatively and quantitatively. This paper tackles the effect of population growth on educational services. To reach the objectives of the research, data related to demographic characteristics were analyzed along with some educational indicators in Lattakia Governorate. Three hypotheses were tested through using SPSS program. Results showed that there is a statistical significant effect of population increase on the portion of teachers for each individual in Lattakia Governorate, and that there is a statistical significant effect of population increase on the portion of classes for each individual. Results also revealed that there is a statistical significant effect of population increase on the portion of school number for each individual in in Lattakia Governorate.